2022
DOI: 10.1002/ejic.202200215
|View full text |Cite
|
Sign up to set email alerts
|

Transition Metal Scaffolds Used To Bring New‐to‐Nature Reactions into Biological Systems

Abstract: As a means to develop new tools to manipulate biological systems, transition metals have been looked upon as an area of high potential due to the bioorthogonality of new-to-nature reactions. To facilitate their incorporation into complex biological systems, researchers have mainly focused on the development of metal catalyst complexes, protein scaffolds, and nanocarriers to protect and preserve the biocatalytic activity of transition metals. The intent of this review is to summarize these structural scaffolds,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 367 publications
0
4
0
Order By: Relevance
“…These are “new‐to‐nature” reactions, a term coined by Arnold, Ward and co‐workers to refer to man‐made reactions not found naturally, that include azide‐alkyne Huisgen cycloaddition, Staudinger‐Bertozzi ligation, transfer hydrogenation, Tsuji–Trost deallylation, depropargylation etc [70] . In recent years, transition metal complexes have been exploited as the key mediator to enable these abiotic reactions within living organisms [71] . As antibacterial agents, a few types of transition metal constructs have been developed and can be broadly grouped as small‐molecule transition metal catalysts, transition metal catalysts encased within proteins scaffolds i.e.…”
Section: Antibacterial Strategies Exploiting Transition Metal Scaffoldsmentioning
confidence: 99%
See 1 more Smart Citation
“…These are “new‐to‐nature” reactions, a term coined by Arnold, Ward and co‐workers to refer to man‐made reactions not found naturally, that include azide‐alkyne Huisgen cycloaddition, Staudinger‐Bertozzi ligation, transfer hydrogenation, Tsuji–Trost deallylation, depropargylation etc [70] . In recent years, transition metal complexes have been exploited as the key mediator to enable these abiotic reactions within living organisms [71] . As antibacterial agents, a few types of transition metal constructs have been developed and can be broadly grouped as small‐molecule transition metal catalysts, transition metal catalysts encased within proteins scaffolds i.e.…”
Section: Antibacterial Strategies Exploiting Transition Metal Scaffoldsmentioning
confidence: 99%
“…[70] In recent years, transition metal complexes have been exploited as the key mediator to enable these abiotic reactions within living organisms. [71] As antibacterial agents, a few types of transition metal constructs have been developed and can be broadly grouped as small-molecule transition metal catalysts, transition metal catalysts encased within proteins scaffolds i.e. artificial metalloenzymes, or transition metal catalysts encapsulated/engrafted with nanocarriers i.e.…”
Section: "New-to-nature" Approachesmentioning
confidence: 99%
“… 1 Within the “toolbox” of bioorthogonal reactions, those involving transition metal catalysis are particularly appealing, as they avoid the need of strained reactants and benefit from the versatility and tuning possibilities of the transition metal reagents. 2 Progress in this area has been sluggish, mostly because of the established notion that transition metal catalysts are not compatible with aqueous and biological milieu. However, recent years have witnessed a substantial growth of the field, especially in the development of uncaging reactions entailing bond-breaking processes, such as the removal of N -alloc groups.…”
Section: Introductionmentioning
confidence: 99%
“…To enhance their biocompatibility, MICs can be spatially conned [26][27][28][29][30] within macromolecular hosts [31][32][33] or designer ligands [34][35][36] (Chart 1A). For example, Ward and coworkers reported that organoiridium complexes incorporated into human carbonic anhydrase II were capable of catalyzing transfer hydrogenation reactions in the periplasm of E. coli bacteria.…”
Section: Introductionmentioning
confidence: 99%